2008
DOI: 10.3892/or.20.1.245
|View full text |Cite
|
Sign up to set email alerts
|

The anti-tumor immune response induced by a combination of MAGE-3/MAGE-n-derived peptides

Abstract: Abstract. Tumor antigen-derived peptides have been widely used to elicit tumor-specific cytotoxic T lymphocytes (CTLs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For example, Gao et al demonstrated that the ratio of activated cytotoxic CD8‐ T cells to inhibitory Tregs in tumor‐infiltrating lymphocytes (TILs) is an independent favorable prognostic factor for disease‐free and overall survival (OS) after surgical resection of HCC . Several human HCC‐specific antigens, including alpha‐fetoprotein (AFP), glypican 3, New York esophageal squamous cell carcinoma 1 (NY‐ESO‐1), melanoma antigen gene A (MAGE‐A), Wilms tumor 1, and human telomerase reverse transcriptase, also have been identified at low levels in patients with HCC. These antigens lead to functional cytotoxic T‐cell response against HCC .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gao et al demonstrated that the ratio of activated cytotoxic CD8‐ T cells to inhibitory Tregs in tumor‐infiltrating lymphocytes (TILs) is an independent favorable prognostic factor for disease‐free and overall survival (OS) after surgical resection of HCC . Several human HCC‐specific antigens, including alpha‐fetoprotein (AFP), glypican 3, New York esophageal squamous cell carcinoma 1 (NY‐ESO‐1), melanoma antigen gene A (MAGE‐A), Wilms tumor 1, and human telomerase reverse transcriptase, also have been identified at low levels in patients with HCC. These antigens lead to functional cytotoxic T‐cell response against HCC .…”
Section: Introductionmentioning
confidence: 99%
“…Identification of these CTL epitopes allows for clinical applications of these peptides as cancer vaccines for patients with MAGE-n + /HLA-A2 + tumors. Our previous study showed that the combination of MAGE-3 and MAGE-n epitopes induced more effective antitumor immune responses than either of the peptides alone (16). In addition, the peptide-specific activity was observed to be in a MHC-restricted manner.…”
Section: Discussionmentioning
confidence: 99%
“…MAGE gene-derived peptides are widely expressed in many tumor and are able to stimulate antigen-specific CTL responses against MAGE-expressing cancer cells, resulting in tumor cell lysis. Therefore, thanks to their effectiveness in preventing and treating diverse cancers, MAGE has been used as a target for cancer immunotherapies [ 97 ]. In this Phase I trial, Morse et al [ 96 ] isolated Dex by ultracentrifugation from peripheral blood mononuclear cells and loaded them with MAGE-A3, -A4, -A10, and MAGE-3DPO4 peptides.…”
Section: Evs In Anti-tumor Immunotherapymentioning
confidence: 99%